Digital Public Administration for Sustainable Development - Burlacu, Sorin; Popescu, Maria Loredana; Diaconu, Amelia; Sârbu, Alexandra (European Journal of Sustainable Development, 2021)
The aim of our research is to highlight the main features and mechanisms of the digitalization of a public administration that would allow the promotion of a sustainable development and a more inclusive society. The proliferation of information and communication technologies in all fields along with the reporting of both economic and social benefits give us hope that these technologies will also find a role in the transformation, efficiency, or progress of public administration. The main research method was the bibliographic study, both descriptive and analytical. Through specialized software tools we highlighted the relationships and correlations between various concepts. The results obtained are encouraging and have highlighted the future courses of action, both theoretical approaches and the exchange of good practices.